Comparison of Nine Meteorological Drought Indices Over Middle Euphrates Region During Period from 1988 To 2017 - A. Alwan, Imzahim; Razzak T. Ziboon, Abdul; G. Khalaf, Alaa (International Journal of Engineering and Technology, 2018)
The aim of this research is compare between nine drought indices and evaluate their performance with respect to predict and monitoring drought over Middle Euphrates region during period from 1988 to 2017.These indices are RDI, Normal SPI, Gamma SPI, Log SPI, CZI, MCZI, RAI, PN, and DI.Season and annual time scale were used to calculate all indices at Dewaniya, Hilla, Karbala, Najaf, and Semawa stations. The Pearson correlation coefficient between nine drought indices were analyzed. Annual and seasonal results illustrated that the maximum value of correlation between RDI and the other indices was noted with Gamma SPI and Log SPI at all stations. In annual time scale, the correlation coefficient reached to (0.99) at all stations except Hilla station, where it reached to (0.98), while in seasonal time scale the correlation coefficient reached to (0.98) at all stations. The RDI, Gamma SPI and Log SPI indices have similarity of classes and frequencies for drought. They also have similarity of frequencies for wet but there are minimum differences between wet classes compared to other indices. The RDI, Gamma SPI and Log SPI are good indices to predict and monitoring drought in study area in comparison to other indices which mentioned above. Â Â